The influence psychological support and well-being, classroom management, and creativity on numeracy skills - Ikwan Wahyudi; Diyah Ratih Fitrianti; Swastoko Galuh Wibowo (LINEAR: Journal of Mathematics Education, 2025)
Numeracy skills are fundamental in mathematics education, yet assessment results continue to reveal areas for improvement. This study investigates the influence of psychological support, psychological well-being, classroom management, and creativity on students' numeracy skills. This study employs a quantitative research method. Data were collected through document analysis of the 2024 National Assessment Public Report for elementary schools and their equivalents. A total sample of 81,824 students was selected based on the availability of complete data on the examined variables. Data analysis was conducted using structural equation modeling with the SEM-PLS approach. The results indicate that all independent variables positively and significantly influence students' numeracy skills, with creativity exerting the most substantial effect and a coefficient of determination of 18.1%. Additionally, psychological well-being partially mediates the relationship between psychological support and numeracy skills. Therefore, a more holistic learning approach is needed to improve numeracy skills by considering psychosocial factors and the learning environment. Theoretically, the study supports the view that numeracy development is not solely cognitive but shaped by affective and contextual dimensions. Practically, it calls for policies and teaching practices that promote psychological well-being, creativity, and supportive learning environments in schools.